Targeting epigenetic regulators as a promising avenue to overcome cancer therapy resistance - Jiawei Song; Ping Yang; Canting Chen; Weiqun Ding; Olivier Tillement; Hao Bai; Shuyu Zhang (Signal Transduction and Targeted Therapy)
Abstract Cancer remains one of the leading health threats globally, with therapeutic resistance being a long-standing challenge across chemotherapy, radiotherapy, targeted therapy, and immunotherapy. In recent years, the association between epigenetic modification abnormalities and therapeutic resistance in tumors has garnered widespread attention, spurring interest in the development of approaches to target epigenetic factors. In this review, we explore the widespread dysregulation and crosstalk of various types of epigenetic modifications, including DNA methylation, histone modifications, and non-coding RNA changes, which interact through complex regulatory networks in tumors. Clinically, single-targeted therapy based on epigenetic modification usually has its limited effect against cancer. However, the combination of epigenetic drugs with other treatment modalities, such as chemotherapy, targeted therapy, or immunotherapy, shows potential for synergistically enhancing efficacy and reducing drug resistance. Therefore, we evaluate the possibility and potential mechanisms of targeting epigenetic modifications to overcome resistance in cancer therapy, and discuss the challenges and opportunities in moving epigenetic therapy into clinical practice. Moreover, the application of multi-omics technologies will aid in identifying core epigenetic factors from complex epigenetic networks, enabling precision treatment and overcoming therapeutic resistance in tumors. Furthermore, the development of spatial multi-omics technologies, by providing spatial coordinates of cellular and molecular heterogeneity, revolutionizes our understanding of the tumor microenvironment, offering new perspectives for precision therapy. In summary, the combined application of epigenetic therapies and the integration of multi-omics technologies herald a new direction for cancer treatment, holding the potential to achieve more effective personalized treatment strategies.